Influence of past breast feeding on pattern and severity of presentation of juvenile idiopathic arthritis. Issue 4 (14th September 2015) - Hyrich, Kimme L; Baildam, Eileen; Pickford, Hannah; Chieng, Alice; Davidson, Joyce E; Foster, Helen; Gardner-Medwin, Janet; Wedderburn, Lucy R; Thomson, Wendy
Abstract : This analysis aimed to study the influence of breast feeding on the pattern and severity of juvenile idiopathic arthritis (JIA) at presentation. The association between ever versus never breast feeding and disease severity at onset was compared in 923 children with JIA recruited to the UK Childhood Arthritis Prospective Study at first presentation to rheumatology. Fifty six per cent of children were ever breast fed (median 3.7 months). Breastfed children reported a lower median age at onset, a lower Childhood Health Assessment Questionnaire (CHAQ), a measure of disease severity, lower parent general evaluation scores and lower pain at presentation. There was a trend towards a higher proportion of breastfed children with rheumatoid factor-negative polyarthritis, but lesser enthesitis-related and psoriatic arthritis. There was a statistically significant inverse association between breast feeding and high CHAQ, even after adjusting for differences in socioeconomic status (adjusted OR 0.61 (95% CI 0.39 to 0.95)). Further work to understand the reasons behind these associations is required.